Identification and preliminary characterization of the 2,5-diphenyloxazole biosynthetic pathway in streptomyces polyantibioticus SPRT - Kemp, Ian Kyle (Department of Molecular and Cell Biology, 2016)
An antibacterial compound produced by the actinomycete, Streptomyces polyantibioticus SPRT, exhibited antibiosis against Mycobacterium tuberculosis H37RvT (the causative agent of tuberculosis), which prompted interest in its biosynthesis. The antibacterial compound was isolated in a previous study and its structure was determined by X-ray crystallography and nuclear magnetic resonance (NMR) to be 2,5-diphenyloxazole (DPO). Based on the structure of DPO, a biosynthetic scheme for the synthesis of this molecule was proposed, whereby a non-ribosomal peptide synthetase (NRPS) condenses a molecule of benzoic acid with 3-hydroxyphenylalanine. The dipeptide is converted to a diphenyloxazole derivative by heterocyclization and a final decarboxylation step leads to DPO. To determine whether the hypothesis pertaining to the DPO biosynthetic pathway was correct, initial efforts were made to identify the genes coding for benzoic acid synthesis and the DPO NRPS in the S. polyantibioticus SPRT genome using PCR amplification, Southern hybridization and sequencing. This led to the identification of 12 unique adenylation (A) domains (of which one was specific for phenylalanine) and a gene, paaK, encoding a phenylacetate CoA-ligase (PA-CoA), putatively involved in benzoic acid biosynthesis. However, no further sequence information could be obtained for the genes encoding the Phe A domain or PA-CoA and similar attempts to identify other NRPS-associated domains, as well as genes involved in benzoic acid synthesis, proved unsuccessful. In light of these difficulties, the S. polyantibioticus SPRT genome was sequenced and a gene cluster was identified as being responsible for the biosynthesis of DPO using a genome mining approach. However, contrary to the hypothesis that a linear NRPS system for DPO biosynthesis would be identified, the gene cluster exhibited a nonlinear arrangement. The core domains are arranged as A-PCP-C (instead of C-A-PCP) and there is also a stand-alone heterocylization domain, a stand-alone thioesterase domain and an acyl-CoA synthetase putatively involved in activating benzoic acid. Furthermore, there are two NRPS domains in the gene cluster that are believed to be inactive. A possible biosynthetic pathway for benzoyl-CoA production, encoded by a separate gene cluster, was identified based on the genome analysis of S. polyantibioticus SPRT. In order to confirm the involvement of the identified genes in DPO biosynthesis, an intergeneric conjugation protocol was developed for the introduction of plasmid DNA into S. polyantibioticus SPRT and subsequent gene disruption experiments. The putative DPO biosynthetic genes were insertionally activated via homologous recombination and the method for isolating DPO was carried out on each of the mutant strains, after which the extracts were assayed for activity against Mycobacterium aurum A+ using TLC-bioautography analysis. The absence of activity against M. aurum A+ in the extracts from mutant strains S. polyantibioticus ΔA99, S. polyantibioticus ΔCYC and S. polyantibioticus ΔACY suggested the involvement of the A domain encoded by gene SPR_53060, the putative heterocyclization domain encoded by gene SPR_53040 and the acyl-coA synthetase encoded by gene SPR_52860 in the biosynthesis of DPO. However, attempts to identify the genes responsible for benzoic acid biosynthesis proved unsuccessful, as gene disruption did not abolish DPO activity in the S. polyantibioticus ΔLAC, S. polyantibioticus ΔPAAK and S. polyantibioticus ΔCIN mutant strains encoding the putative D-lactate dehydrogenase encoded by gene SPR_60250, the PA-CoA ligase (paaK) encoded by gene SPR_46390 and the cinnamate CoA ligase encoded by gene SPR_60150, respectively. Based on the genome annotation analysis and gene disruption studies, a model for DPO biosynthesis is proposed. At this stage, the model cannot account for the source of benzoic acid, as in vivo gene disruption experiments disproved both of the hypotheses on how benzoic acid is synthesized in S. polyantibioticus SPRT. However, alternative hypotheses regarding the mechanism of benzoic acid biosynthesis in S. polyantibioticus SPRT are proposed and are suggested as the place to start in future studies to elucidate the production of this unusual starter unit in DPO biosynthesis. Furthermore, the identification of the gene cluster responsible for DPO biosynthesis may be used for combinatorial biosynthetic studies to create derivatives of DPO that might be used in the treatment of drug resistant tuberculosis. Lastly, the S. polyantibioticus SPRT genome sequence could be explored for the identification of antibiotic gene clusters for other potential antitubercular antibiotics that this organism produces.